How do technological innovation and digital infrastructure affect material footprint? the inverted U-shaped effect in resource-rich economies - Li, Shundian; Borojo, Dinkneh Gebre (Frontiers in Environmental Science, 2025)
IntroductionEfficient management of natural resources is a fundamental goal of the SDGs, aimed at supporting responsible production and consumption practices. Technological innovation (TI) and digital infrastructure (DI) serve as crucial tools that influence effective resource management. However, limited focus has been directed toward assessing the non-linear relationships between the material footprint (MFP), TI, and DI. This research seeks to provide fresh perspectives on the influence of TI and DI on MFP, utilising data from resource-rich economies (RE) spanning 1990 to 2021.MethodsGiven the characteristics of the data, we employ the pooled mean group-autoregressive distributed lag (PMG/ARDL) model. Furthermore, for sensitivity analysis, we apply instrumental variables (IV) and methods of moments quantile regression (MMQR) techniques to address distributional heterogeneity and endogeneity issues. The investigation is repeated while accounting for green innovation (GI) to examine the effects of environmentally-associated TI on MFP.Results and discussionThe findings reveal that the coefficients of the level and squared terms of TI and DI are positive and negative in the long run, respectively. Therefore, TI and DI exhibit a non-linear influence on MFP, suggesting an inverted U-shaped link between TI, DI, and MFP over the long term. Thus, TI and DI contribute to a resource curse up to threshold values of 2.827 and 2.081, after which they enhance resource efficiency in RE, implying that greater investment in TI and DI yields better outcomes for harnessing resource efficiency than lesser investment. Lastly, both small and large changes in GI have a robust negative impact on MFP. These findings carry significant policy implications for enhancing TI and DI, aimed at fostering responsible natural resource management per SDGs 8 and 12, thus ensuring the efficient and sustainable use of natural resources.